Investigation of nanoyarn preparation by modified electrospinning setup. Issue 19 (16th January 2017) - Levitt, Ariana S.; Knittel, Chelsea E.; Vallett, Richard; Koerner, Michael; Dion, Genevieve; Schauer, Caroline L.
ABSTRACT: Higher ordered structures of nanofibers, including nanofiber‐based yarns and cables, have a variety of potential applications, including wearable health monitoring systems, artificial tendons, and medical sutures. In this study, twisted assemblies of polyacrylonitrile (PAN), polyvinylidene fluoride trifluoroethylene (PVDF‐TrFe), and polycaprolactone (PCL) nanofibers were fabricated via a modified electrospinning setup, consisting of a rotating cone‐shaped copper collector, two syringe pumps, and two high voltage power supplies. The fiber diameters and twist angles varied as a function of the rotary speed of the collector. Mechanical testing of the yarns revealed that PVDF‐TrFe and PCL yarns have a higher strain‐to‐failure than PAN yarns, reaching 307% for PCL nanoyarns. For the first time, the porosity of nanofiber yarns was studied as a function of twist angle, showing that PAN nanoyarns are more porous than PCL yarns. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44813. Abstract :